How should digital tools for writing be evaluated? : Reflections from digital pedagogies and applied linguistics - Curry, Niall (Journal of Academic Writing, 2023)
The use of digital tools in academic literacies remains an emerging field, having advanced greatly in recent years. This dialogue responds to Schcolnik (2018), by arguing the benefits of considering the use of such tools in light of advances in digital pedagogies and applied linguistics. Going beyond understanding how academic writing developers engage with digital tools, an important next step is to consider whether their use of such tools is effective.